The Paradox of Green Identity in Social Media Thrift Culture - Anisa Rizki Sabrina; Berliana Rohmah Nirmala; Ratna Triwurian Danu; Fairuza Arindra (COMMENTATE: Journal of Communication Management, 2026)
Thrift culture has grown in popularity among Gen Z on platforms like TikTok and Instagram, often portrayed as an ethical and eco-friendly alternative to fast fashion. This study critically investigates how digital thrift content simultaneously promotes sustainability while encouraging new forms of consumption. Using a netnographic approach, 40 social media posts were analyzed between April and June 2025, focusing on hashtags such as #thriftinghaul and #sustainablefashion. The research draws on symbolic interactionism and digital self-presentation theory to examine how sustainability is represented and interpreted. Findings reveal four key patterns: thrift is used as a digital identity marker; green values are often aestheticized; excessive purchases are morally justified as secondhand; and algorithmic visibility amplifies content that normalizes high-volume consumption. Rather than challenging fast fashion, thrifting online may reproduce similar consumerist logics under a sustainable label. This study contributes to debates in digital communication and sustainability by highlighting how social media environments shape, reframe, and sometimes distort ecological values. It calls for a more critical lens in environmental messaging—one that recognizes the influence of digital aesthetics, platform dynamics, and symbolic consumption. In doing so, the study encourages deeper reflection on authenticity in sustainability communication.